Briquettes of Sugarcane Bagasse and Eucalyptus spp Sawdust: Characterization and Hygroscopic Equilibrium - Alo, Livia L.; Konishi, Paula A.; Belini, Gabriela B.; Silva, Juliette P. da; Martins, Mariana P.; Nakashima, Gabriela T.; Caraschi, Jose C. [UNESP]; Yamaji, Fabio M. (Brazilian Chemical Soc, 2017)
The knowledge of the hygroscopic behavior is an important factor in the characterization of compacted biomass. The aim of this study was to characterize blends of sawdust and sugar cane bagasse briquettes in different storage conditions. The proportions of sawdust and sugarcane bagasse were determined so that the blends reached moisture contents that defined 4 treatments: T1 (22.5%): 30% sawdust and 70% sugar cane bagasse; T2 (17.5%): 50% sawdust and 50% sugar cane bagasse; T3 (13.8%): 65% sawdust and 35% sugar cane bagasse e T4 (10.0%): 80% sawdust and 20% sugar cane bagasse. After compaction the briquettes were subjected to three different conditions: A1 (63% UR), A2 (75% UR) e A3 (45% UR). They were produced 30 briquettes for each treatment. The briquettes were left in storage for 10 days. The analysis of the briquettes was performed by determining the weight variation, longitudinal expansion and mechanical strength. It was observed that the briquettes of treatment T3 (13.8%) showed the best results on the longitudinal expansion (3.45%) and obtained the highest mechanical resistance (1.10 MPa). The storage of briquettes in A1 (63% UR) and A3 (45% UR) resulted in lower longitudinal expansion and greater mechanical resistance. The results confirmed that the addition of sawdust, in different proportions, in the compaction of sugarcane bagasse, decreased the high hygroscopicity of sugarcane bagasse, resulting in dimensional stability and resistant briquettes, and it is an alternative to energetic reuse of these wastes.
Keywords: Bioenergy; biomass; residues